Life stories: the value of memory, the power of the word - Criado, María Jesús (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
Very different circumstances (the  end of an era, a model of  knowledge which  has  shown its  weaknesses, a  social science  which questions itself  and   searches  for new  paths) contribute to the recovery  of one  of the more  classical  methodologies used  by the social  sciences, the life-story, giving it new  meaning and  content. The subjective point of view, the inside look, holds its place again in social science. In the context  of epochal change marked by  the  appearance of new  social  tensions generated  by  the  process   of  globalization,  some  of the more  trascendental issues take  shape  within  the framework  of the new  migrations. The diversity and significance of the dilemmas and conflicts derived from   these show this phenomenon to be the center of one of the most extensive and complex fields of  study. From this perspective, it is held that the  use  of the  biographic approach not  only  contributes to a greater knowledge of the problem because  it incorporates the subject’s  point of view,  but  that  it can also have other functions.